If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=x-14+7x
We simplify the equation to the form, which is simple to understand
-6=x-14+7x
We move all terms containing x to the left and all other terms to the right.
-1x-7x=-14+6
We simplify left and right side of the equation.
-8x=-8
We divide both sides of the equation by -8 to get x.
x=1
| .5(6x+10)=20 | | q+70=55 | | -35-x=31+5x | | 3t+3=6t+9 | | (5x^2+1)(6x^2+4)=1 | | G/3=3.9 | | 3(x-5)-4(2x-3)=7 | | (2y+3y)2= | | x-.85x=32.89 | | 6a-10+5a=6a+20 | | 5+1.5(2m-1)=0.5 | | 5n+35+50=160 | | 58=1/2-x | | Sqrt(-7-7x)+3=10 | | 2/5x+1/10=1/2(x+4) | | 6a-10a+5a=6a+20 | | 58=1/2x | | 11pq(5p-7q+4)= | | 8x/4=12 | | -20+-3x=-12x+7 | | 1/2(4-x)=2/5 | | 43-n+16=44 | | 22=9+6(h+8) | | x-4=156 | | 1-4+5=2 | | 3x^2=-16 | | V^2+8v=13 | | 30x+70y=50 | | (-3.9)(-6.4)= | | 7m+5=68-2m | | (4,2)m=-5/3 | | 3x^3/8=16 |